2018
DOI: 10.3892/mmr.2018.9273
|View full text |Cite
|
Sign up to set email alerts
|

Low‑frequency ultrasound and microbubbles combined with simvastatin promote the apoptosis of MCF‑7 cells by affecting the LATS1/YAP/RHAMM pathway

Abstract: Ultrasound scanning has widespread used in clinical practice and also has therapeutic applications. Simvastatin is a statins that is able to competitively inhibit the activity of 3-hydroxy-3-methylglutaryl-coenzyme A reductase. The aim of the present study was to investigate the roles and mechanisms of low-frequency ultrasound (LFU) and microbubbles combined with simvastatin on MCF-7 cell growth and apoptosis. Cell viability, apoptosis and cell cycle were evaluated using an MTT assay and flow cytometry, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Microscopy-based techniques are ideal for managing multiple time scales since imaging rates can vary from real-time imaging (a few frames per second) allowing the evaluation of drug influx and cellular responses to high-speed (150 000 fps) imaging which can resolve the release of model drugs from microbubbles and streaming effects and even to ultra-high-speed imaging (up to 25 million fps), making it possible to resolve the microbubble oscillations during ultrasound exposure. , Other methods can be used to evaluate the consequences of microbubble–cell interactions during or after ultrasound treatment . For example, the integrity of cell membranes and intercellular junctions can be measured using electrical sensing techniques (TMC and TEER). , The proteomic and transcriptomic changes in the exposed tissue can be analyzed using Western blots, ELISA assays, and PCR analysis. , The effects can be studied in further detail quantitatively using flow cytometry and qualitatively using electron and atomic force microscopy. Nevertheless, owing to this inherent complexity, the interpretation and integration of these different techniques remains a significant challenge.…”
Section: Part 2: Microbubble–cell Interactions To Release and Deliver...mentioning
confidence: 99%
“…Microscopy-based techniques are ideal for managing multiple time scales since imaging rates can vary from real-time imaging (a few frames per second) allowing the evaluation of drug influx and cellular responses to high-speed (150 000 fps) imaging which can resolve the release of model drugs from microbubbles and streaming effects and even to ultra-high-speed imaging (up to 25 million fps), making it possible to resolve the microbubble oscillations during ultrasound exposure. , Other methods can be used to evaluate the consequences of microbubble–cell interactions during or after ultrasound treatment . For example, the integrity of cell membranes and intercellular junctions can be measured using electrical sensing techniques (TMC and TEER). , The proteomic and transcriptomic changes in the exposed tissue can be analyzed using Western blots, ELISA assays, and PCR analysis. , The effects can be studied in further detail quantitatively using flow cytometry and qualitatively using electron and atomic force microscopy. Nevertheless, owing to this inherent complexity, the interpretation and integration of these different techniques remains a significant challenge.…”
Section: Part 2: Microbubble–cell Interactions To Release and Deliver...mentioning
confidence: 99%
“…LATS1 is an upstream protein of YAP and adjusts YAP by removing it from the nuclear chamber. 28 A study has showed that LATS proteins are notably down-expressed in breast cancer and non-small cell lung cancer. 29 Dephosphorylated YAP allows its entry into nucleus where it activates the transcription of proproliferative and anti-apoptotic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the RA‐V(1) group, after the blocking of Hippo signalling pathway, the expression of LATS1 and the extent of YAP phosphorylation decreased, the expression of Beclin 1 increased, expression of LC3‐II/I and Casepase‐3 increased, and the number of autophagic vesicles increased, thus inhibiting proliferative capacity and promoting apoptotic and autophagic ability. LATS1 is an upstream protein of YAP and adjusts YAP by removing it from the nuclear chamber . A study has showed that LATS proteins are notably down‐expressed in breast cancer and non‐small cell lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…First, in vitro studies have shown that application of low-intensity ultrasound can regulate the Hippo pathway and YAP/TAZ. [190][191][192] Second, in vitro studies in Schwann cells have shown that ultrasound regulates signaling pathways upstream of the Hippo pathway. 193,194 Finally, extensive studies provide evidence that low-intensity ultrasound activates and promotes Schwann cell proliferation, a major outcome of the Hippo pathway (reviewed in 195 ).…”
Section: Mechanical Based Therapiesmentioning
confidence: 99%